The Influence of Product Innovation, Country of Origin, and Product Knowledge on Purchase Intention: The Mediating Effect of the Brand Attitude - Reswari, Rianti Ardana B1024141008 (Jurnal Manajemen Update, 2018)
Globalization succeed to broadening consumer choice with the help of technology that provide sufficient variety of information. The consequence faced by companies is the competition whether for domestically and internationally became intense compared than before globalization era arrives. Chinese brands are recently increasingly popular overseas and reaching out to compete with global scale brand, as well as global consumers continuously searching to the companiesâ€™ origin for the newest product innovations yet cheapest price in the market. Then consumers started to gain attention and intention in Chinese brands. Brand attitude is formed because it can be beneficial for a company. While customer value is referring to the comparison of benefits and costs from a customer perspective. The product innovation is one of the benefits that consumer receive after buying certain products. In addition, the country of origin and product knowledge is information utility that customer employ to indicate a perceived product quality.Â Basing on research objective in which to analyze the influence of product innovation, country of origin, and product knowledge on purchase intention through brand attitude. The close-ended questionnaires were handed to 100 respondents. The data calculated using SmartPLS 3.2.7, all of the hypotheses are accepted it means it has positive direct effects among variables. This study is exemplified the strongest correlation between brand attitude and purchase intention. Even though the observed relationship between product knowledge and brand attitude has the lowest tendency but it still reflects relationship for both variables. The findings noted that to create more favorable brand attitude, a company need to focusses on efforts that able generating storage of customer memory about the specification of a product. Significantly, company could cash cow the brand name as it is getting good acceptance in the market. The limitation of study was small number of samples, geographic territory, and theoretical support.Â